2021
DOI: 10.1155/2021/5590623
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Huangqi Shengmai Yin on Type 1 Diabetes-Induced Cardiomyopathy by Improving Myocardial Lipid Metabolism

Abstract: Diabetic cardiomyopathy (DCM) is one of the many complications of diabetes. DCM leads to cardiac insufficiency and myocardial remodeling and is the main cause of death in diabetic patients. Abnormal lipid metabolism plays an important role in the occurrence and development of DCM. Huangqi Shengmai Yin (HSY) has previously been shown to alleviate signs of heart disease. Here, we investigated whether HSY could improve cardiomyopathy caused by type 1 diabetes mellitus (T1DM) and improve abnormal lipid metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…39 The leakage of CK, CK-MB and LDH into the serum indicates myocardial damage. 40,41 Then we detected the leakage of myocardial damage indicators CK, CK-MB, and LDH into the serum, and found that FX reversed the increase of CK, CK-MB and LDH in STZinduced diabetic rats, which indicates that FX can improve heart injury. STZ-induced diabetic rats after 8 weeks were shown to have different degrees of abnormality in left ventricular diastolic and systolic functions.…”
Section: Discussionmentioning
confidence: 93%
“…39 The leakage of CK, CK-MB and LDH into the serum indicates myocardial damage. 40,41 Then we detected the leakage of myocardial damage indicators CK, CK-MB, and LDH into the serum, and found that FX reversed the increase of CK, CK-MB and LDH in STZinduced diabetic rats, which indicates that FX can improve heart injury. STZ-induced diabetic rats after 8 weeks were shown to have different degrees of abnormality in left ventricular diastolic and systolic functions.…”
Section: Discussionmentioning
confidence: 93%
“…Diabetic heart lipid metabolism is impacted due to changes in the expression of transporters involved in FA uptake (34), alterations in the PPAR signaling pathway during FA oxidation (35), accumulation of lipotoxicity, and activation of the MAPK signaling pathway (36). Lipid metabolism alterations in type 2 diabetes mellitus (T2DM) have been widely reported, and notably, lipid accumulation in type 1 diabetes mellitus (T1DM) has also been reported by relevant studies (37)(38)(39).…”
Section: Fatty Acid Oxidationmentioning
confidence: 99%
“…A recent study has reported that HSY could effectively inhibit the development of DCM in diabetic mice model. It was observed that HSY alleviated cardiac injury, and improved heart rate, while reduced QT interval and QRS complex by repairing unnormal myocardial lipid metabolism through increasing the expression of PPAR‐α, p‐AMPKα, SIRT1, PGC‐1α, and CPT‐1, and decreasing the activity of CD36 (Cao et al, 2021). The results indicated HSY alleviated DCM by promoting fatty acid oxidation while reducing fatty acid uptake.…”
Section: Traditional Chinese Medicine Inhibits Cvd By Regulating Fatt...mentioning
confidence: 99%